Association between pregnancy status and COVID-19 clinical manifestations, morbidity, and mortality among unvaccinated women in Metro Manila, Philippines: A multi-center prospective cohort study - Erlidia F. Llamas-Clark; Maria Esterlita T. Villanueva-Uy; Faye Stephanie S. Cagayan; Francisco M. Heralde, III; Mayan U. Lumandas; Jeremiah F. Feliciano; Paulyn Jean B. Rosell-Ubial; Emmanuel S. Baja (Clinical Epidemiology and Global Health, 2023)
Background: The presenting clinical manifestations and the influence of pregnancy on the progression and symptomatology of COVID-19 among Filipina women are still understudied. This study assessed the association between pregnancy status and COVID-19 clinical manifestations, morbidity, and mortality among unvaccinated women in Manila, Philippines. Methods: This multi-center prospective cohort study ascertained the pregnancy status and presence of SARS-CoV-2 with a validated health questionnaire. Generalized linear models with a Poisson distribution were fitted to estimate the association between pregnancy status and the clinical manifestations, morbidity, and cause-specific mortality from COVID-19, adjusting for confounding factors. Results: Non-pregnant women were observed to report thermoregulatory, respiratory, musculoskeletal, and digestive symptoms more frequently than pregnant women. Being pregnant vs. not pregnant was associated with clinical manifestations of sore throat and being feverish. In addition, pregnancy is less likely to result in hospitalization and mortality among unvaccinated Filipinas. Conclusion: Pregnancy status indicates influence on hospitalization prevalence and mortality among unvaccinated Filipino women. Research on the longitudinal nature and post-recovery persistence of the symptoms of COVID-19 among women is recommended.